Theoretical simulation of different 3D separator geometries for lithium-ion batteries - Miranda, D. (2020)
The battery separator is an essential component of batteries and affects their cycling performance. In this work, the effect of different 3D geometries of the battery separator on battery performance was studied keeping the same volume. It was observed that the different geometries affect the cycling performance, the best geometry being the perforated one that cycled up to 90 C. The cycling performance is affected by parameters such as the separator thickness and the electrolyte volume. Through the control of the battery separator geometry it is possible to obtain high performance lithium-ion batteries.